Obscuur Libel dalam Gugatan Harta Warisan yang Dilakukan Isteri Ketiga berdasarkan UU No.50 Tahun 2009 - Sophia Fitriana (Bandung Conference Series: Law Studies, 2022)
Abstract. Marriage for the community aims to maintain and continue offspring, for the happiness of the family or relative household, but not a few of these goals are stopped because of the breakdown of a marriage caused by several factors and the legal consequences of the breakup of the marriage. In the case of divorce, when there is a joint property dispute, the most important thing is the fact or event by knowing objectively where the case is. The true incident will be known by the judge from the evidence. In addition, in carrying out their judicial functions, judges must pay attention to justice, legal certainty, and expediency. The decision must be fair, contain legal certainty, but the decision must also contain benefits for the person concerned and the community. Inheritance cases that were not accepted at the Indramayu Religious Court because of an obscure lawsuit (obscur libel). As for the reason the lawsuit cannot be accepted, because the posita and petitum in the lawsuit do not support each other or the argument of the lawsuit is contradictory, including the object in dispute it is not clear what type, and the incompleteness of the parties may result in the non-acceptance of the inheritance claim. So basically, if the lawsuit does not meet the formal and material requirements, the court will reject the lawsuit. The type of research conducted by the author is library research using normative legal research. Normative collection techniques, namely research on legal principles. Data analysis used qualitative analysis in the form of content analysis or descriptive analysis. Abstrak. Pernikahan bagi masyarakat bertujuan untuk mempertahakan dan meneruskan keturunan, untuk kebahagiaan rumah tangga keluarga atau kerabat, namun tidak sedikit tujuan tersebut terhenti karena terputusnya suatu perkawinan yang disebabkan oleh beberapa factor dan menimbulkan akibat hukum dari putusnya perkawinan tersebut. Dalam kasus perceraian bilamana terjadi sengketa harta bersama, yang terpenting adalah fakta atau peristiwanya dengan mengetahui secara obyektif duduknya perkara. Peristiwa yang sebenarnya akan diketahui hakim dari pembuktian. Selain itu dalam menjalankan fungsi peradilannya, hakim harus memperhatikan keadilan, kepastian hukum, dan kemanfaatan. Putusan itu harus adil, mengandung kepastian hukum, tetapi putusan itu harus pula mengandung manfaat bagi yang bersangkutan dan masyarakat. Perkara waris yang tidak diterima di Pengadilan Agama Indramayu karena gugatan yang kabur (obscur libel). Adapun sebab gugatan tidak dapat diterima, karena posita dan petitum dalam gugatan tidak saling mendukung atau dalil gugatannya kontradiksi, termasuk obyek yang disengketakan tidak jelas apa jenisnya, dan kurang lengkapnya para pihak dapat mengakibatkan tidak diterimanya gugatan waris tersebut. Jadi intinya, apabila gugatan tidak memenuhi syarat formil dan materilnya, maka pengadilan akan menolak gugatan tersebut. Jenis penelitian yang dilakukan penulis adalah library research menggunakan penelitian hukum normatif. Teknik pengumpulan normatif, yaitu penelitian terhadap asas-asas hukum. Analisis data menggunakan analisa kualitatif berupa content analisis atau deskriptif analisis.